Jugurtha resistance to the Roman occupation (112-105 B.C) - Bouzid Doua (Social Empowerment Journal, 2022)
The Jugurtha War is an important stage of the Roman occupation of the Maghreb. After the occupation of Carthage in 146 BC, the Romans clashed this time with a resistance claimed by Prince Jugurtha, who was able to organize the ranks of the Numidian cavalry and soldiers and showed great courage and good planning, as he was able to inflict defeats on the Roman forces in more than A battle, however, the weapon of treachery eventually turned the scales and returned the tide of the Romans, and after the defeat of Jugurtha, the Romans put them in the Kingdom of Numidia and annexed part of it to their possessions, while they installed on the remaining part Prince Goda (brother of Jugurtha), who was weak and subject to the Romans, and the third Loyal to Mauritania, it was granted to King Bocuse I in return for the services he rendered to the Romans in alliance with them against his brother-in-law Jugurtha.